Clinical question: How to manage symptoms of hypogonadism in patients after androgen abuse?. (17th February 2022) - Botman, Esmée; Smit, Diederik L.; de Ronde, Willem
Abstract: Androgen abuse is relatively common amongst young (amateur) bodybuilders. After cessation, the hypothalamic‐pituitary‐gonadal (HPG) axis—which has been suppressed by the androgens—needs time to recover. The endogenous testosterone production often recovers within 3 months, however, prolonged or permanent post‐androgen abuse hypogonadism (PPAAH) has been described. There is no widely accepted definition nor is its pathogenesis completely elucidated. To date it is a subject of debate whether PPAAH is a separate entity, reflecting irreversible damage to essential components of the HPG axis inflicted by long‐term exposure to high doses of androgens. Alternately, it may be the result of longer than expected suppressive effects of androgen depots, undisclosed ongoing androgen abuse or undiagnosed unrelated disorders. Due to the lack of scientific evidence, the management of PPAAH is challenging. By combining clinical experience with evidence from the recent literature, a suggested outline of the management of androgen‐abuse‐induced hypogonadism are given.